Critical Discourse Analysis In Indonesia Lawyers Club (ILC) "RKUHP CONTROVERSY" On TV ONE - L.M Ady Marlan Wardoyo Hasim; Lia Maulia Indrayani; Ypsi Soemantri (Wanastra: Jurnal Bahasa dan Sastra, 2020)
On 25 September 2019, Indonesia Lawyers Club (ILC) have made themes Rancangan Kitab Undang Undang Hukum Pidana controversy or RKUHP controversy. ILC discusses several chapters that invite the pros and cons in the interpersonal community of the article concerning the insult to the President and Vice President, article on the possession of supernatural powers to commit a criminal offense, article on poultry breeding, article on demonstrating contraceptives, articles on abortion, and other. In the critical paradigm, the use of language in the media is intentional and has a specific purpose. Seeing this, researchers are interested in seeing the discourse built in the talk show. The researchers used a critical discourse analysis technique model (Teun van Dijk) and found that ILC built a discourse that article RKUHP serves the interests of the Government. The RKUHP intervenes in the privacy of the community, and RKUHP discriminates against certain groups. This discourse also shows the definition and positioning of the ILC position on the participants of the production discourse. ILC placed Karni Iliyas as the dominant moderator so that his reality could be accepted by the public as truth. using the technique of text analysis, social cognition, and context, researchers found a discourse built by ILC confirming the view that the RKUHP invites pros and cons in society. Researchers have also found that the ILC conversion of the RKUHP is influenced by government interests.